Development of Augmented Reality -Based Booklets as Learning Media for Students' Learning Interest in Global Warming Material - Wulandari, Ratna Wahyu; Aslamiyah, Mughiz Syuwaibatul; Zahro, Anisyarofatu; Munifah; Daud, Dalila Haji (Proceeding International Conference on Education, 2025)
In order to boost students' interest in learning about global warming, this project intends to create an instructional booklet based on augmented reality (AR). Employing the Research and Development (R&D) method with the ADDIE model, the study was conducted at MTs Al Khoiriyah Baron Nganjuk with the participation of 21 seventh-grade students. Observations indicated that science learning was largely dominated by textbooks and teacher explanations, with limited use of interactive media, which led to low student engagement. Based on needs analysis questionnaires, 78% of students were found to have a visual learning preference, showing greater interest in instructional materials with videos and colored images. The developed AR booklet incorporates colorful illustrations and interactive quizzes designed to aid understanding of complex scientific concepts. Expert validation confirmed the high validity of this media (92%-93%), deeming it highly feasible for educational use. Effectiveness testing through pre- and post-assessments showed a significant increase in students' comprehension, with an average N-Gain score of 0.82, indicating that the AR-based media was highly effective in enhancing student interest and understanding of global warming material. The AR technology enables students to visualize greenhouse gas effects and the impact of global warming on oceans, thus offering an interactive, engaging learning experience that makes science learning more effective and appealing.